Avaliação da função da musculatura do assoalho pélvico de primíparas um a três anos após o parto : estudo transversal - Soares, Iára Pimentel (Universidade Federal de São Carlos, 2016)
The objective of this study was to compare the function, vaginal pressure and electromyography activity of the pelvic floor muscles between nulliparous and primiparous after vaginal delivery or cesarean, one to three years after delivery. Cross-sectional study, conducted at the Women's Health Research Laboratory at Federal University of São Carlos. Sixty volunteers were included between 18 and 40 years old, sexually active; in the case of primiparous, have given birth at 37 weeks gestation or more for at least one year and at a maximum of three years. The procedures included anamnesis, vaginal palpation, perineometry and surface electromyography of the pelvic floor muscles. To analyze the reproducibility of digital palpation and perineometry, it was used the intraclass correlation coefficient calculation and standard error of measurement. Nonparametric variables were analysed using Kruskal-Wallis test or Mann-Whitney test. One-way ANOVA was used for the parametric variables. It was adopted a significance level of 5%. No significant difference was found between groups in relation to the function of the pelvic floor muscles evaluated by digital palpation (p = 0.75), perineometry (p = 0.25) and surface electromyography (0.465). The function of the pelvic floor muscles between primiparous from one to three years after spontaneous vaginal delivery, after cesarean and in nulliparous was similar. The recovery of pelvic floor muscle function after pregnancy and delivery should be investigated in future studies.
Keywords: Parto; Cesárea; Diafragma pélvico; Eletromiografia; Parturition; Cesarean section; Pelvic floor muscle function; Electromyography; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL